Speech Acts in Jokowi’s Campaign Speeches - Khairunnisa Siregar; Zainuddin Zainuddin (Universitas Negeri Medan, 2016)
The objectives of this study are to describe the types of speech acts used in Jokowi’s campaign speeches, to elaborate the realization of Jokowi used illocutionary act in campaign speeches, to know the reason of using illocutionary act. This study was conducted by descriptive qualitative research. The data of the research are the utterances of Jokowi’s speeches. The source of the data was Jokowi’s campaign speeches. The technique for collecting data is documentary technique. The technique of data analysis was interactive model by using Miles and Huberman. The findings show all types of speech acts were used in Jokowi’s campaign speeches, namely: locutionary act, illocutionary act can be classified into five parts; there were assertive, directive, commissive, expressive, declarative and the last types was perlocutionary act. The realization of illocutionary act used in Jokowi’s campaign speeches, the directive speech act was used in form of warning, commanding, promising, offering, questioning, requesting. The reasons of using illocutionary act in Jokowi’s campaign speeches are to point out or to identify what the speaker mean from his utterance, which influence of meaning and information of the speech and to get information clearly from Jokowi’s campaign speeches. Keywords: speech acts, campaign, campaign speeches